Broilers Welfare and Economics under Two Management Alternatives on Commercial Scale - Fouad, Manal A.; Razek, Abeer H. Abdel; Badawy, El Sayed M. (International Journal of Poultry Science, 2008)
An experiment was conducted to clarify the effect of two management systems (cages Vs floor system) on welfare status and economics of broiler chicks. Two commercial flocks each of about 12375 day old Hubbard broiler chicks of mixed sex were housed in two fully environmentally controlled pens (cage and floor pens) from 0-6 weeks of age. Welfare was assessed through bird’s performance, behavior, fearfulness and Heterophil: lymphocyte ratio (HLR). Compared to cage reared group, floor reared broilers recorded significantly heavier final body weight, body weight gain, better feed conversion and lower mortalities throughout the whole rearing period (0-6 weeks). Behavioral data showed that, caged birds were more often standing and stereotyped drinking, however floor reared group showed more walking, feeding and pecking. Total prevalence of gait problems and (HLR) were significantly higher in cage than floor group. Economic analysis revealed that, rearing broilers on floor was more profitable than cage rearing system. Data obtained in this experiment suggested that the welfare status of broilers was compromised under cage conditions as indicated by impaired performance, increased mortalities, higher prevalence of leg problems, stereotyped behavior and higher (HLR). In conclusion, cages are not recommended as a management system for rearing broilers from both the economic and welfare points of view.